Action of permethrin on Rhipicephalus sanguineus (Latreille, 1806) (Acari: Ixodidae) semi-engorged females: Morpho-physiological evaluation of salivary glands - Nodari, Elen Fernanda [UNESP]; Roma, Gislaine Cristina [UNESP]; Scopinho Furquim, Karim Christina [UNESP]; Bechara, Gervasio Henrique [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Elsevier Gmbh, Urban & Fischer Verlag, 2012)
Currently the most effective method of tick control is the use of acaricides, among which stands out permethrin (active ingredient of acaricide Advantage (R) Max3, Bayer), a neurotoxic pyrethroid. However, assessments of their effects on other tick systems such as glandular are still scarce. Thus, this study provides information, through histochemical techniques, about the toxic effect of this pyrethroid on the morphophysiology of salivary glands of semi-engorged Rhipicephalus sanguineus females exposed to different concentrations of permethrin (206, 1031, and 2062 ppm). The results showed that permethrin caused significant changes in the salivary gland metabolism accelerating the process of glandular degeneration, an event which would occur naturally and with great intensity only in the final engorgement stage. Furthermore, this study pointed out that permethrin reduces the salivary gland secretion ability through a drastic reduction of proteins, lipids, and polysaccharides in acinar cells. These changes impair the females to finalize the feeding process, what indirectly affects the reproductive process. (c) 2012 Elsevier GmbH. All rights reserved.
Keywords: Rhipicephalus sanguineus; Permethrin; Salivary gland; histochemistry; Cytotoxicity